MENINGKATKAN KETERAMPILAN MEMBUAT SAPU LIDI MELALUI METODE LATIHAN PADA ANAK TUNAGRAHITA RINGAN KELAS D.V - Azwir, Yarmis Hasan, Martias, Z (Jurnal Penelitian Pendidikan Khusus, 2013)
This research aim to to: 1) to describe the implementation process of learning to make a broom through training methods and 2) Prove that if the method can improve the repetition exercises make broom mild mental retardation of the child in class D.V SLB Al-Mirza Barung Barung Belantai. This type of research is classroom action research done in the form of collaboration with colleague. The subject is three children, mild mental retardation and a DV class teachers. Data obtained through observation, tests. Then analyzed qualitatively and quantitatively. The results showed that 1) the process of learning to make a broom by using exercises done in two cycles. Cycle I conducted 10 meetings and the second cycle with five meetings. Each cycle begins with planning, implementation (initial activity, core and end), observation, and analysis and reflection. 2) The results of the study by using the method of exercise of the ability to make a broom stick apparently increased. It can be seen from the data in the prior action the ability to do 25 steps to make a broom stick is RD (32%), KT (42% and TO (52%). After the first cycle, the child began to increase the ability of RD (66), KT ( 68%) and TO (827%). while the second cycle TO've all (100%) were able to make a broom stick, RD (92%) and KT (98%). Concluded that the method can improve the skills training makes children broom mild mental retardation SLB class V in Al-Mirza-barung barung Belantai. keterampilaan recommended to teachers in order to use the method in the teaching of other skills training.